Coagulation and fibrosis in chronic liver disease. Issue 12 (20th November 2008) - Calvaruso, V; Maimone, S; Gatt, A; Tuddenham, E; Thursz, M; Pinzani, M; Burroughs, A K
Abstract : In the hepatic tissue repair mechanism, hepatic stellate cells (HSCs) are recruited at the site of injury and their changes reflect paracrine stimulation by all neighbouring cell types, including sinusoidal endothelial cells, Kupffer cells, hepatocytes, platelets and leucocytes. Thrombin converts circulating fibrinogen to fibrin, promotes platelet aggregation, is a potent activator of endothelial cells, acts as a chemoattractant for inflammatory cells and is a mitogen and chemoattractant for fibroblasts and vascular smooth muscle cells. Most of the cellular effects elicited by thrombin are mediated via a family of widely expressed G-protein-coupled receptors termed protease activated receptors (PARs). All known members of the PAR family stimulate cell proliferation/activation in a rat HSC line. Thrombin receptors are constitutively expressed in the liver, and their expression increases in parallel with the severity and/or the duration of liver disease. In human studies, thrombotic risk factors were found to be independently associated with the extent of fibrosis; severity of hepatitis C virus (HCV)-associated liver disease appears to be less in patients with haemoihilia when compared with those with HCV alone. Several studies, based mostly on rat models, demonstrate that anticoagulants or antiplatelet agents prevent hepatic necrosis and fibrosis by acting on HSCs. These drugs could be therapeutic agents in patients with chronic liver disease and specific studies should be initiated.